Trichoderma as a Model to Study Effector-Like Molecules - Ramírez-Valdespino, Claudia A.; Casas-Flores, Sergio; Olmedo-Monfil, Vianey (Frontiers in Microbiology, 2019)
Abstract Plants are capable of perceiving microorganisms by coordinating processes to establish different forms of plant-microbe relationships. Plant colonization is governed in fungal and bacterial systems by secreted effector molecules, suppressing plant defense responses and modulating plant physiology to promote either virulence or compatibility. Proteins, secondary metabolites, and small RNAs have been described as effector molecules that use different mechanisms to establish the interaction. Effector molecules have been studied in more detail due to their involvement in harmful interactions, leading to a negative impact on agriculture. Recently, research groups have started to study the effectors in symbiotic interactions. Interestingly, most symbiotic effectors are members of the same families present in phytopathogens. Nevertheless, the quantity and ratio of secreted effectors depends on the microorganism and the host, suggesting a complex mechanism of recognition between the plant and their associated microorganisms. Fungi belonging to Trichoderma genus interact with plants by inducing their defense system and promoting plant growth. Research suggests that some of these effects are associated with effector molecules that Trichoderma delivers during the association with the plant. In this review, we will focus on the main findings concerning the effector molecules reported in Trichoderma spp. and their role during the interaction with plants, mainly in the molecular dialogue that takes place between them.